The Influence of Organizational Culture on Employee Performance with Job Satisfaction as a Mediating Variable: (Study on Government Employees of Ternate Island District) - Safril, Fitri Cahyani; Alhadar, Fadhliah M.; Buamonabot, Irfandi (International Journal of Business, Law, and Education, 2026)
This study aims to examine how organizational culture influences employee performance, with job satisfaction serving as a mediating variable among village and sub-district office employees on Ternate Island. It employed a quantitative approach, selecting 108 respondents through saturated sampling. Primary data were collected via questionnaires and analyzed using the Structural Equation Modeling–Partial Least Square (SEM-PLS) technique. The results indicated that organizational culture positively and significantly impacts employee performance. Additionally, organizational culture also positively and significantly affects job satisfaction. Job satisfaction was shown to have a positive and significant influence on employee performance and to mediate the relationship between organizational culture and employee performance. These findings contribute to human resource management research in the public sector and highlight the importance of fostering a strong, supportive organizational culture to enhance job satisfaction and employee performance in local government settings.